Diagnostic challenges of adult T-cell leukemia/lymphoma in North America – a clinical, histological, and immunophenotypic correlation with a workflow proposal. Issue 5 (4th May 2018) - Licata, Michael J.; Janakiram, Murali; Tan, Stephanie; Fang, Yanan; Shah, Urvi A.; Verma, Amit K.; Wang, Yanhua
Abstract: Adult T-cell leukemia-lymphoma (ATLL) is caused by human T-cell lymphotropic virus type 1 (HTLV-1) and little is known about ATLL endemic to the Caribbean basin and Latin America, designated as western ATLL (W-ATLL). Due to extensive systemic involvement and nonspecific clinical presentation, the initial diagnosis in this cohort can be very challenging. We have diagnosed 60 patients with W-ATLL over a 14-year period. ATLL involves the peripheral blood, bone marrow, and cerebrospinal fluid (CSF) in 98, 87, and 52% cases, respectively; while lymphadenopathy, pulmonary infiltrates, splenomegaly, and hepatomegaly was present in 90, 82, 48, and 45% patients, respectively. While 87% patients developed hypercalcemia only 28% had lytic bone lesions. We propose that any diagnosis of a peripheral T-lymphoproliferative disorder should result in a comprehensive review of the patient's endemic, laboratory information, HTLV-1 testing for proper diagnosis, and identification due to the varied manifestations of this disease.